Partial anomalous left pulmonary artery in heterotaxy syndrome. A case report and review of literature. (March 2021) - Betancourt, Lauren Gabriel; Singh, Harinder R.; Agarwal, Arpit
Abstract: Partial anomalous left pulmonary artery in association with congenital heart defects is a rare anomaly that can cause compression of the tracheobronchial tree. We report a case of partial anomalous left pulmonary artery causing compression of the left mainstem bronchi in a patient with heterotaxy syndrome. To the authors' knowledge, this is the first reported case of a partial anomalous left pulmonary artery causing compression of the left mainstem bronchi in a patient with heterotaxy syndrome. We also reviewed other reported cases of partial anomalous left pulmonary artery with and without tracheobronchial compression. Highlights: Partial anomalous LPA is an accessory left pulmonary artery originating from the RPA, in addition to the normal LPA. Partial anomalous LPA is a rare anomaly that can cause compression of the tracheobronchial tree. Heterotaxy syndrome is a rare disorder characterized by abnormal lateralization and isomerism of thoraco-abdominal organs Partial anomalous LPA causing compression of mainstem bronchi in a patient with heterotaxy syndrome has never been reported A review of other reported cases of partial anomalous LPA with and without tracheobronchial compression is also presented